Cost allocation for the problem of pollution reduction: a dynamic cooperative game approach. Issue 1 (1st January 2018) - Luqman, Muhammad; Peng, Sui; Huang, Shaoan; Bibi, Amina; Ahmad, Najid
Abstract: This paper studies CO2 emissions at a global level. The authors use Dynamic Optimisation to derive the minimum penalty cost on countries every single time. They then use an Imputation Distribution Procedure to allocate the minimum penalty cost among countries. Their work provides the extension of the Shapley value cost allocation as a penalty to reduce CO2 emissions. The paper has implications for how to provide initiatives to improve cooperation on reducing CO2 emissions at an international level. Results show that a reduction in cost of only one country can be harmful for other countries. In this way, some countries can end up or worse off in a case where all countries experience a uniform decrease in their penalty cost. Therefore, the findings of this work suggest a low penalty-cost scenario that helps the countries fight for pollution reduction and provide fruitful links for policy-makers. They show that the Clean Development Mechanism (CDM) of the Kyoto Protocol could be implemented by the Shapley value cost allocation.